The Impact of GAAP on Fiscal Decision Making A Review of Twelve Years' Experience with Accrual and Output-based Budgets in New Zealand - Barnes, Cheryl (OECD Publishing, 2004)
This paper reviews the theory and the rhetoric for accrual accounting and budgeting by government. Reference is made to generally accepted accounting practice (GAAP) in New Zealand. An historical summary is provided of 12 years of accrual budgets and, using this as a base, assessments are made of the actual benefits that have been achieved...